Evaluate the following limit, using L'Hospital's rule if necessary lim (x+1)e^(-2x) X->+infinity can't figure this one out...
Follow Math Help Forum on Facebook and Google+
Originally Posted by thecount Evaluate the following limit, using L'Hospital's rule if necessary lim (x+1)e^(-2x) X->+infinity can't figure this one out... This is the same thing as $\displaystyle \lim_{x\to\infty}\frac{x}{e^{2x}}+\lim_{x\to\infty }\frac{1}{e^{2x}}$ The second limit goes to zero. Try to show that the first one also goes to zero.
Last edited by Chris L T521; Nov 30th 2008 at 07:22 PM.
View Tag Cloud